DDE KG Editor: A data service system for knowledge graph construction in geoscience - Hou, Chengbin; Liu, Kaichuang; Wang, Tianheng; Shi, Shunzhong; Li, Yan; Zhu, Yunqiang; Hu, Xiumian; Wang, Chengshan; Zhou, Chenghu; Lv, Hairong (Geoscience data journal, 2024)
Deep‐time Digital Earth (DDE) is an innovative international big science program, focusing on scientific propositions of earth evolution, changing Earth Science by coordinating global geoscience data, and sharing global geoscience knowledge. To facilitate the DDE program with recent advances in computer science, the geoscience knowledge graph plays a key role in organizing the data and knowledge of multiple geoscience subjects into Knowledge Graphs (KGs), which enables the calculation and inference over geoscience KGs for data mining and knowledge discovery. However, the construction of geoscience KGs is challenging. Though there have been some construction tools, they commonly lack collaborative editing and peer review for building high‐quality large‐scale geoscience professional KGs. To this end, a data service system or tool, DDE KG Editor, is developed to construct geoscience KGs. Specifically, it comes with several distinctive features such as collaborative editing, peer review, contribution records, intelligent assistance, and discussion forums. Currently, global geoscientists have contributed over 60,000 ontologies for 22 subjects. The stability, scalability, and intelligence of the system are regularly improving as a public online platform to better serve the DDE program. DDE KG Editor is developed to help geoscience experts around the world cooperate in constructing high‐quality large‐scale Geoscience Professional Knowledge Graphs (GPKGs). DDE KG Editor comes with several distinctive features such as collaborative editing, peer review, contribution record, intelligent assistance, and discussion forums. Currently, global experts have contributed over 60,000 ontologies for 22 subjects, and the scale is still growing. The constructed GPKGs in DDE KG Editor are free for non‐commercial use to boost knowledge sharing and applications in geoscience.